The Dollar Spot Susceptibility of 25 Bentgrasses is Consistent across Five States in the Central USA. Issue 1 (24th January 2019) - Thompson, Cole; Zhang, Qi; Kennelly, Megan; Stier, John; Blume, Christopher; Christians, Nick; Fry, Jack; Martin, Dennis; Ostrander, Jesse; Rincker, Keith; Settle, Derek; Soldat, Douglas
Abstract : Core Ideas: Genetic differences in dollar spot susceptibility among bentgrasses are consistent across the Central U.S.A. at putting green and fairway mowing heights and with or without fungicides. 'Kingpin' or 'Memorial' creeping bentgrass had the least dollar spot injury and 'Crystal BlueLinks', 'Declaration', 'L‐93', and 'SR1150' were consistently in the same statistical grouping as these cultivars. Golf course superintendents should use National Turfgrass Evaluation Program or similar data from as near their location as possible to assess seasonal cultivar performance, but relative dollar spot susceptibility should be applicable across broader regions if nearby data are not available.